2014
DOI: 10.1371/journal.pone.0089716
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology and Antimicrobial Susceptibility of Clinical Staphylococcus aureus from Healthcare Institutions in Ghana

Abstract: The objective of this study was to determine the antimicrobial susceptibility patterns and clonal diversity of clinical Staphylococcus aureus isolates from Ghana. A total of 308 S. aureus isolates from six healthcare institutions located across Northern, Central and Southern Ghana were characterized by antibiotyping, spa typing and PCR detection of Panton Valentine leukocin (PVL) genes. Methicillin-resistant S. aureus (MRSA) were confirmed by PCR detection of mecA gene and further characterized by SCCmec and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

31
97
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(131 citation statements)
references
References 37 publications
31
97
3
Order By: Relevance
“…Also Gülmez et al, 2012 found MRSA to be 97 (34%) out of 285 S. aureus isolates. The observed MRSA prevalence among clinical isolates in Ghana is similar to those reported in European countries with low MRSA prevalence, such as the Scandinavian countries and The Netherlands (Egyir et al, 2014). …”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…Also Gülmez et al, 2012 found MRSA to be 97 (34%) out of 285 S. aureus isolates. The observed MRSA prevalence among clinical isolates in Ghana is similar to those reported in European countries with low MRSA prevalence, such as the Scandinavian countries and The Netherlands (Egyir et al, 2014). …”
Section: Resultssupporting
confidence: 82%
“…The prevalence of MRSA (3%) was lower than those reported in other African countries such as Nigeria (20%), Algeria (45%) and in a multicenter study (15%) involving five major African towns. Egyir et al, 2014 attributed the low MRSA frequency reported in their study to the low consumption of antimicrobial agents such as fluoroquinolones and third generation cephalosporins in Ghana, because they are expensive and are usually prescribed for acute infections. Usage of the aforementioned antimicrobial agents has been shown to correlate with an increase in MRSA prevalence (Egyir et al, 2014).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…A recent study showed S. aureus and MRSA carriage prevalence of 14% and 10% among inpatients (not diagnosed with HIV) at Korle Bu teaching hospital in Ghana [8]. In this same geographic setting, spa type t355 and t084 together with high prevalence of PVL (21-60%) were predominantly detected [8,9]. There is however, no information on S. aureus carriage strains among HIV-infected patients in Ghana.…”
Section: Introductionmentioning
confidence: 97%